Correction: Healthy lifestyle behaviors are major predictors of mental wellbeing during COVID-19 pandemic confinement: A study on adult Arabs in higher educational institutions. - Hashem A Kilani; Mo'ath F Bataineh; Ali Al-Nawayseh; Khaled Atiyat; Omar Obeid; Maher M Abu-Hilal; Taiysir Mansi; Maher Al-Kilani; Mahfoodha Al-Kitani; Majed El-Saleh; Ruba M Jaber; Ahmad Sweidan; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0243524.].